Uji Patogenisitas Isolat Bakteri Indigenous (Bacillus thuringiensis) terhadap Serangga Hama Kubis (Crocidolomia binotalis Zell) - Christina L. Salaki; Jesmandt Situmorang; Langkah Sembiring; Niken Handayani (Universitas Atma Jaya Yogyakarta, 2009)
Pathogenicity of 34 indigenous B. thuringiensis isolates against C. binotalis were determined. The pathogenicity test was conducted by using leaf dipped method with various spore concentrations. Third instar larvae of C. binotalis were used as insect test. Mortality data of test larvae were used to determine the pathogenicity of the isolates in terms of 72 hours LC50 by using probit analysis. The results of experiments showed YPPA 1. was the most pathogenic isolate, producing 72 hours LC50 = 9.5 x 103 spore.ml-1 with LT50 (1.5 x 107 spore.ml-1) of 24.6 hours while the ACH 2.3 was found to be the least pathogenic isolate with 72 hours LC50 = 2.3 x 106 spore.ml-1 and LT50 (1.5 x 107 spoore.ml-1) of 40.7 hours. The shortest LT50 (1.5 x 107 spore.ml-1 was found to be 18.2 hours produced by TUS.1 with 72 hours LC50 = 3.9 x 105 spore.ml-1 whereas the longest LT50 (1.5 x 107 spore.ml-1) was found tobe 83.2 hours produced by the SLK 4.1 with 72 hours LC50 = 3.1 x 104 spore.ml-1. Therefore, it can be concluded that both YPPA.1 and TUS.1 isolates are potential candidate to be developed for biological control agent.